Ants are more than just curious bystanders to some flowers—they act as significant pollinators - Das, Susmita; Das, Amlan (Frontiers in Insect Science, 2023)
Abstract Ant-plant associations are ubiquitous and highly diverse in almost all terrestrial environments, resulting in complex ecological networks. While ant-plant mutualism is frequent, ant-mediated pollination is uncommon, and only a few investigations have demonstrated their role in pollination. Thus, the topic of ant-mediated pollination requires revision to assess its significance in pollination biology. Ants are familiar floral visitors, but their impact on plant reproductive fitness is rarely acknowledged; nonetheless, numerous flower-visiting ants have been investigated for their involvement in promoting floral development and hybrid vigour in crops. Over the last four decades, the scientific works of literature on ants' involvement in pollination are summarized; the diversity of pollinating ants to various host plants, the ant-plant pollinating networks, and seasonal patterns of ant-mediated pollination are all compiled. Ants generally forage to flowers in quest of nectar and other sustenance, and in doing so, they pollinate flowers they encounter. This review identified the pollination networks between ants and plants at the species and family levels. Pollination is often affected by a number of aspects, including the flower's sex, its ovary position, the inflorescence it bears, and the time of year. The available literature demonstrates that ants only visit the inflorescences of the same species to promote cross-pollination, a process known as 'geitonogamy'; however, we conclude that ants may visit different inflorescences of different plants in the field. If ant-mediated self-pollination had been the norm, there might have been less selection pressure to acquire self-compatibility; nonetheless, stories of ants' cross-pollination pushed ants to co-evolve with the pollinating flowers. It indicates that ants are more than just curious bystanders to some flowers; they act as significant pollinators.